Enhancing human resources for maize research and development in West and Central Africa: a networking approach - Badu-Apraku, Baffour; Fakorede, M.A.B.; Ajala, S. (2004)
The West and Central Africa Collaborative Maize Research Network (WECAMAN) was instituted with the ultimate goal to help improve maize (Zea mays L.) production in West and Central Africa (WCA). One objective of the Network is to enhance the research capacity and capability of the participating national research systems (NARS). This objective is being achieved through training courses and workshops, monitoring tours, consultation visits and a visiting scientist program. The Network has conducted these activities for about 20 years in 11 member countries with financial support from the U.S Agency for International Development (USAID) and more recently, the United Nations Development Program(UNDP) and International Fund for Agricultural Development (IFAD). The Network has used human resources and facilities available in the sub-region to conduct all training courses and workshops. Nearly 50 technicians and 150 scientists have participated in the Network's training courses and workshops. Preliminary assessment of WECAMAN's activities indicates that the technicians and scientists have greatly improved their research skills.